Tanggung Jawab Perusahaan Jasa Pengiriman Barang Di Kota Jambi - Siregar, Yolanda; Suhermi, Suhermi (Universitas Jambi, Fakultas Hukum, 2024)
This study aims to identify and analyze the implementation of the responsibilities of PT. Yatama Air Cargo Prioritas Jambi branch against consumer losses in shipping goods as well as to find out and analyze the causes of losses for consumers and efforts to resolve consumer losses in shipping goods. The problem that will be examined is how the implementation of the responsibilities of PT. Yatama Air Cargo Prioritas Jambi branch against consumer losses in shipping goods and what are the obstacles that cause losses for consumers and efforts to resolve consumer losses in shipping goods. The research method used is Juridical Empirical research, namely legal research regarding the application of normative legal provisions directly to every legal event that occurs in society. The results of this study indicate that PT. Yatama Air Cargo Prioritas Jambi branch has not carried out its responsibilities in full, in terms of fulfilling responsibilities there are several inhibiting factors that cause damage, delays and loss of goods which can harm consumers. The settlement efforts are carried out peacefully without going through the courts. Where consumers who experience losses can claim in the form of compensation, the amount of which has been regulated in the terms of the goods delivery agreement, both insured and uninsured goods and PT. Yatama Air Cargo Prioritas Jambi branch is ready to accept complaints about losses experienced by consumers and will provide a solution by way of deliberation between the two parties.